Personal, interpersonal, and cultural predictors of stages of cigarette smoking among adolescents in Johannesburg, South Africa. (24th May 2006) - Brook, J S; Morojele, N K; Brook, D W; Zhang, C; Whiteman, M
Abstract : Objective: This study examined the personal, parental, peer, and cultural predictors of stage of smoking among South African urban adolescents. Design: A cross-sectional design was employed. A stratified random approach based on census data was used to obtain the sample. Analyses were conducted using logistic regression. Setting: The study took place in communities in and around Johannesburg, South Africa. Subjects: Participants consisted of 731 adolescents in the age range of 12–17 years old. The sample was 47% male and 53% female, and contained four ethnic classifications: white, black, Indian, and "coloured" (a South African term for mixed ancestry). Methods: A structured, in-person interview was administered to each participant in private by a trained interviewer, after obtaining consent. Main outcome measures: The dependent variables consisted of three stages of smoking: non-smoking, experimental smoking, and regular smoking. The independent measures were drawn from four domains: personal attributes, parental, peer, and cultural influences. Results: Factors in all four domains significantly predicted three different stages of smoking. Personal attributes (internalising and externalising) distinguished among the three stages. Parental factors (for example, affection) reduced the odds of being a regular smoker compared with an experimental smoker or non-smoker, but did not differentiate experimental smokers from non-smokers. Findings from the peer domain (for example, peer substance use) predicted an increase in the risk of being a regular smoker compared with an experimental smoker or non-smoker. In the cultural domain, ethnic identification predicted a decrease in the risk of being a regular smoker compared with an experimental smoker, whereas discrimination and victimisation predicted an increase in the risk of being an experimental smoker compared with a non-smoker. Conclusions: All the domains were important for all four ethnic groups. Four psychosocial domains are important in distinguishing among the three stages of smoking studied. Some predictors differentiated all stages of smoking, others between some of the stages of smoking. Therefore, intervention and prevention programmes which are culturally and linguistically sensitive and appropriate should consider the individual's stage of smoking.